Beyond scarcity,Powerty and the global water crisis (New York, 2006)
The 2006 Human Development Report focuses on water and human development. Water is central to the realization of human potential. It is a source of life for people and for the planet. Clean water and sanitation have a profound bearing on health and human dignity. Inequalities in access to clean water for drinking and to water as a productive input, reinforce wider inequalities in opportunity. With competition for water intensifying, there is a danger that poor and vulnerable communities will become increasingly marginalized. The twin challenge facing governments and donors is to accelerate progress towards universal access to water and sanitation; and to ensure that water management policies strengthen the rights of poor households to access water resources.
Keywords: Water resources development,Cung cấp nước,Water supply,Sustainable development,Phát triển bền vững